Integrating WASAKA Local Wisdom Into Scientific Learning to Enhance Pre-Service Physics Teachers’ Competence - Salam, Abdul; Setiawan, Agus; Putra, Aminuddin Prahatama; Ruyadi, Yadi (Universitas Lambung Mangkurat, 2026)
Strengthening the academic competence of pre-service physics teachers requires instructional designs that not only emphasize scientific processes but also draw on local wisdom as a meaningful learning context. This study examined the effectiveness of integrating the scientific approach with WASAKA local wisdom in improving the academic competence of physics education students. A quantitative method with a pre-experimental design was employed during the second semester of the 2024/2025 academic year. The study participants consisted of 9 students in the limited trial and 21 students in the extensive trial. Academic competence was assessed using pretest–posttest essay questions, while students’ responses were analyzed through an ARCS-based questionnaire. The results indicate a clear improvement in students’ academic competence following the intervention. The gain scores were in the moderate category for both the limited trial (g = 0.55) and the extensive trial (g = 0.43), suggesting a meaningful increase in academic performance. Improvements were observed across all competence indicators, with relatively higher achievement in conceptual understanding and experimental design skills, whereas mathematical reasoning showed a more moderate increase. Student responses were highly positive across all ARCS dimensions, reflecting strong attention, relevance, confidence, and satisfaction with the learning experience. These findings confirm that integrating the scientific approach with WASAKA local wisdom offers a promising contextual learning strategy in physics teacher education, with further emphasis recommended on scaffolding to strengthen mathematical reasoning.